Pengaturan terhadap Pengusahaan Air Bawah Tanah yang Dilakukan oleh Masyarakat - Desak Putu Setyarina; I Putu Gede Seputra; Luh Putu Suryani (Warmadewa Press, 2020)
The water has an important role in survival of all living things on this earth. Water in underground is a natural resources and the damage that occurs can cause widespread impact and repair is quite difficult. In order to guarantee the fair used and exploitation of groundwater, a permit is required. However, in the use and exploitation of groundwater, there are people and industrial parties who did not have a permit from the government related to the prevailing laws and regulations. The purpose of this research is to find out how the regulation of underground water exploitation is carried out by the community and what are the legal consequences of unlicensed underground water exploitation. The method used in this research is normative method and analysis of legal interpretation and descriptive analysis. Data sources are primary and secondary data. The research approach used in this research is an invitation-only approach and a legal concept analysis approach. The technique of conducting legal materials is carried out by means of literature study which is legal materials are collected then processed using systematic interpretation analysis. The results of this research are first, in regulating the exploitation of groundwater, the authority and legal basis used by the government as a reference in granting permits. Second, the result of not having a permit to use ground water is the sealing of the location or place and the imposition of imprisonment in accordance with the applicable laws, namely Law Number 11 of 1974 concerning Irrigation and other regulations in accordance with the respective Regional Regulations.